Effects of patient-centered communication on anxiety, negative affect, and trust in the physician in delivering a cancer diagnosis: a randomized, experimental study - Zwingmann, Jelena; Schmier, Johann-Wilhelm Adam; Keller, Monika (Cancer, 2017)
BACKGROUND When bad news about a cancer diagnosis is being delivered, patient-centered communication (PCC) has been considered important for patients' adjustment and well-being. However, few studies have explored how interpersonal skills might help cancer patients cope with anxiety and distress during bad-news encounters. METHODS A prospective, experimental design was used to investigate the impact of the physician communication style during a bad-news encounter. Ninety-eight cancer patients and 92 unaffected subjects of both sexes were randomly assigned to view a video of a clinician delivering a first cancer diagnosis with either an enhanced patient-centered communication (E-PCC) style or a low patient-centered communication (L-PCC) style. Participants rated state anxiety and negative affect before and immediately after the video exposure, whereas trust in the physician was rated after the video exposure only. Main and interaction effects were analyzed with generalized linear models. RESULTS Viewing the disclosure of a cancer diagnosis resulted in a substantial increase in state anxiety and negative affect among all participants. This emotional response was moderated by the physician's communication style: Participants viewing an oncologist displaying an E-PCC style were significantly less anxious than those watching an oncologist displaying an L-PCC style. They also reported significantly higher trust in the physician. CONCLUSIONS Under a threatening, anxiety-provoking disclosure of bad news, a short sequence of empathic PCC influences subjects' psychological state, insofar that they report feeling less anxious and more trustful of the oncologist. Video exposure appears to be a valuable method for investigating the impact of a physician's communication style during critical encounters. Cancer 2017;123:3167-75. © 2017 American Cancer Society.